Improvement of leaf rust resistance in bread wheat variety DWR162 (Triticum aestivum L.) through marker assisted selection - Yadawad, Arati; Hanchinal, R. R. Hanchinal; Nadaf, H. L.; Desai, S.A.; Biradar, Suma; Rudranaik, V. (The Indian Journal of Genetics and Plant Breeding, 2016)
SCAR markers SCS1302 and SCS421 linked to leaf rust resistance genes Lr24 and Lr28 used in the present study genetically improved a bread wheat variety DWR162 using marker assisted selection. Evaluation of BC1F2 generation under field conditions indicated that plants with both Lr24 and Lr28 were superior in yield and its components and leaf rust resistance. Twenty six DUS characters used for identification of plants showed close resemblance with recipient variety DWR 162.The availability of a combination of the two major leaf rust resistance genes in desirable background would encourage the genetically enhanced DWR 162 with leaf rust resistance for its cultivation in a large area.